Observing Enables Deeper Learning for Disaffected Learners - Fiona J McDonnell; Eric Crivac (Middle Grades Review, 2023)
Post-Covid, upon returning to the classroom, many students, but most especially those from among our more vulnerable populations, have difficulty collaborating and communicating with each other and reconnecting with their learning. We describe how a learning exploration that positioned struggling rising sixth-graders as cricket explorers, who would become cricket experts by observing the habits and behaviors of crickets in their care, nurtured their capacities for collaboration and communication and created a community of deeper learning, for both the students and teacher. That all students have opportunities for deeper learning is a matter of social justice. The exploration took place as a co-curricular activity in a four-week summer scholars program and involved nine students, five boys and four girls.
Keywords: learning exploration; observing; deep learning; crickets; disaffected learners